Activated carbon derived from biomass combustion bottom ash as solid sorbent for CO2 adsorption - Gorbounov, Mikhail; Petrovic, Ben; Ozmen, Serap; Clough, Peter T. (Elsevier, 2023)
Climate change and global warming, caused mainly by the anthropogenic CO2 emissions, has been recognised to be the biggest threat to global ecosystems. Replacing fossil fuels with sustainable biomass for heat and power generation is a key tool in our fight against climate change. Such combustion, however, generates large quantities of ash which, unlike the coal counterparts, are yet to find major applications in industry. This leads to challenging waste management and thus, necessitating urgent measures to valorise this increasing waste stream. However, producing activated carbon from biomass combustion ash allows for not only effective waste valorisation into value-added products, but also to prepare a sorbent for post-combustion carbon capture from an abundant and cheap source that is readily available for in-situ application (hence, minimising overall costs). This work has focused on preparation and activation of industrial-grade biomass ash-derived porous carbon via an economical direct method, followed by an extensive characterisation of its textural properties as well as an evaluation of the CO2 uptake of both the virgin and the activated carbonaceous sorbents. The final sample was selected based on an extensive optimisation campaign aiming towards maximisation of yield and CO2 uptake. The optimum activated sample adsorbed 0.69 mmol/g, thus, nearly doubling the adsorption capacity of the virgin biomass combustion bottom ash-derived carbon.
Keywords: Post-combustion Carbon Capture; Adsorption; Biomass Combustion Ash; Bottom Ash; Activated Carbon